Termos do Turismo em artigos acadêmicos em inglês: um estudo terminológico - Fontella, Joni Márcio Dorneles (2023)
Academic articles published in journals are one of the main ways of accessing scientific knowledge produced in the most diverse areas. Reading this genre is paramount in the context of teaching and learning in Higher Education, since the access to updated scientific production is a positive factor in the education of students. Research within the scope of lexical studies, on one hand, has shown the existence of an academic vocabulary, which would be similar in different fields of knowledge, but, on the other hand, they highlight the need for carrying out studies that address the specificities of each area. Considering that terms are part of the academic vocabulary (NATION, 2013), in this research we investigated the Tourism sector, having as driving forces the following questions: 1) what are the most frequent terms in academic articles? 2) how to develop a pedagogical material to teach these terms in ESP contexts? In this perspective, the main objective of the research was to identify the recurring terms of Tourism in English in academic articles in the area and organize them into subareas, in order to use them in didactic proposals. To do so, we outlined the following specific objectives: 1) to draw up a list of the most recurrent Tourism terms in the corpus; 2) to verify whether the selected terms are more recurrent in the Academic Word List (AWL) (COXHEAD, 2000), or in the General Service List (GSL) (WEST, 1953); 3) to develop activities focusing on terminological issues, considering the context of Tourism and the interfaces with grammar; 4) to create a didactic material for undergraduate students in Tourism, and related areas, in book and app formats, which presents the most recurrent terms in academic articles in the area. We used the Corpus Linguistics methodology, using the WordSmith Tools 7.0 Program, the AWL (COXHEAD, 2000) as an academic vocabulary reference, and the GSL (WEST, 1953), as a reference for fundamental English vocabulary. This is a corpus-based, qualitative research, which is based on Terminology (CABRÉ, 1993, 2005; HOFFMANN, 2015; KRIEGER; FINATTO, 2020; KRIEGER, 2001; FINATTO; ZILIO, 2015; TAGNIN; BEVILACQUA, 2013; ZAVAGLIA et al. 2020), and in studies of Teaching English for Specific Purposes (ESP) (BELCHER, 2009; CELANI, 1988, 2005; DUDLEY-EVANS; ST JOHN, 2003; HUTCHINSON; WATERS, 1987; PALTRIDGE, 2001; RAMOS, 2008). We had the premise that there were terms of Tourism that do not configure in the works used as reference. The investigation showed the incidence of terms present in the AWL, and we verified that many of them are part of the fundamental vocabulary of the English language (GSL). However, the study showed many terms that were not part of any of the reference lists, which shows that there is a gap that can serve as object for future investigations. As a result of the research, we created a textbook in which the terms of Tourism are presented divided into subareas such as Food and Beverage, Transportation, Money and Finance, Hotels and Accommodation, among others. In addition, we developed an application that has the same content as the book.